Calibrator for Temperature Measurement Device with Raspberry Pi-Based Interface - Iswanto; Megantoro, Prisma; Senzas, Devita Via (International journal of innovative technology and exploring engineering, 2019)
The article discuss about designing a Raspberry Pi 3-Based OHP Temperature Calibrator. This device used to callibrate temperature measurement device with GUI-based (Graphic User Interface). The device has been programmed on Raspberry Pi 3 with Python programming language. This research was done by and recycled over head projector (OHP), designing and conducting sensory characterization analysis and uncertainty analysis on temperature calibrator. The method used in this research is heuristic method, where this method is used in sensor characterization analysis. After the characterization done, obtaining the specifications of each sensor, temperature calibrator instrument then tested to determine the amount of uncertainty of the instrument that has been designed. The result of the homogeneity for fifth test points are 6 °C, 5 °C, 5 °C, 8 °C, and 16 °C. The results of the sensor characterization test show that the accuracy and precision of all sensors are more than 99%. The sensitivity values for the four sensors are 11.68 mV /°C, 12.34 mV /°C, 11.24 mV /° C, and 11.50 mV /° C. The correlations and linearity of all sensors are more than 97% also. And the response of time of the four sensors to the heat source are 1.61 °C/s, 1.13°C/s, 1.17 ° C / s, 1.00 °C/s. the uncertainties for sensor 1 are (132 ± 0.7)°C, sensor 2 (132 ± 0.6)°C, sensor 3 (132 ± 0.7)°C, and sensor 4 (132 ± 0.7)°C. Based on the research, it can be concluded that Raspberry Pi based temperature calibrator instrument has a good accuracy level, and the effective temperature for calibration is at maximum temperature, that is 132°C.